Analysis of Leading Sectors as Supporting the Economy with the Location Quotient, Shift Share, and Klassen Typology Methods in Sukabumi, West Java - Muhammad Fauzan; Ignatia Martha Hendrati (Trunojoyo University of Madura, 2023)
Regional economic development aims to facilitate employment opportunities or job opportunities in large numbers for the local area. In an effort to realize this goal, to obtain regional development initiatives, collaboration between the regional government and the local community must be carried out. Therefore, the participation of local governments and residents who are willing to interpret the capacity of the resources needed to develop and design the regional economy. This study aims to examine the economic sectors in Sukabumi Regency that are unique, have potential, and can be improved to promote economic growth. For Sukabumi Regency and West Java Province over a five-year period, this study uses secondary data from the Central Bureau of Statistics. between the years 2016 - 2020. The leading sector analysis techniques used through 3 stages are Location Quotient, Shift Share, Typology Klassen. The results of this study indicate that from the results of the analysis of leading sectors to support the economy in Sukabumi Regency, there are 10 basic sectors. besides that there are 8 sectors in quadrant 1, 2 sectors in 2nd quadrant, 4 sectors in 3rd quadrant, 3 sectors in 4th quadrant.